Cardiovascular Diseases in the Urban community - an analysis of 1064 referrals from Family Physicians (University Heart Journal, 2008)
This retrospective observational study was done in a private consultation practice form July 2004 to December 2007. A total of 1064 patients were referred by family physicians mainly from the locality but also from other districts. This study was done to see the magnitude of problem involving cardiovascular diseases in the urban community. Â University Heart Journal Vol.4(1) January 2008